2018
DOI: 10.1002/dc.24037
|View full text |Cite
|
Sign up to set email alerts
|

A comparison study of the reporting systems for salivary gland fine needle aspirations: Are they really different?

Abstract: Background Recently a new system for reporting salivary gland fine‐needle aspiration (FNA) cytology was proposed, the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC). Herein, we evaluated diagnostic accuracy of salivary gland FNA, comparing the system previously used in our hospital with the Milan system. Methods Salivary gland specimens obtained between 2011 and 2017 were reclassified according to MSRSGC. Risk of malignancy for each diagnostic category was determined. Diagnostic yield of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
3
22
1
Order By: Relevance
“…The RON and the ROM were 93.5% and 41.9%, respectively. The ROM for the SUMP category of submandibular FNA cases was similar to the ROM of 42% in a meta‐analysis review and slightly higher than the 35% target rate of the MSRSGC and the 37.5% rate in a comprehensive literature review, even though significant variation is expected for this indeterminate category as well (ROM, 37.5% ± 24.7%) . Although the ROMs of AUS (28%) and SUMP (42%) overlapped or were close in our study and others, the RONs of AUS (48%) and SUMP (94%) were very different (Table ), and this was in keeping with the definitions of AUS (indefinite for a neoplasm) and SUMP (diagnostic of a neoplasm but an uncertain type) and supported different approaches for the management of these categories (eg, repeat FNA vs upfront surgery).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The RON and the ROM were 93.5% and 41.9%, respectively. The ROM for the SUMP category of submandibular FNA cases was similar to the ROM of 42% in a meta‐analysis review and slightly higher than the 35% target rate of the MSRSGC and the 37.5% rate in a comprehensive literature review, even though significant variation is expected for this indeterminate category as well (ROM, 37.5% ± 24.7%) . Although the ROMs of AUS (28%) and SUMP (42%) overlapped or were close in our study and others, the RONs of AUS (48%) and SUMP (94%) were very different (Table ), and this was in keeping with the definitions of AUS (indefinite for a neoplasm) and SUMP (diagnostic of a neoplasm but an uncertain type) and supported different approaches for the management of these categories (eg, repeat FNA vs upfront surgery).…”
Section: Discussionsupporting
confidence: 73%
“…In this study, 21.4% of submandibular FNA cases (157 of 734) were diagnosed as nondiagnostic, and this was much higher than the maximum target rate of 10% suggested by the MSRSGC and the 13.5% reported for this category by Song et al Moreover, in 2 separate comprehensive reviews of the literature on salivary gland FNA conducted by Wei et al and Farahani and Baloch, the nondiagnostic rates ranged from 1.1% to 7.8% and from <1% to 44%, respectively . In addition, our study showed that there was high variability in the nondiagnostic rates between institutions, which ranged from 0% to 50%, with 7 of the 15 institutions having nondiagnostic rates ≤ 10%.…”
Section: Discussioncontrasting
confidence: 52%
“…Three studies formally compared the MSRSGC to previous reporting schemes 21,29,40 . Two of these showed that implementation of the MSRSGC increases the rate of unsatisfactory or ND FNA cases 21,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The most notable difference between the MSRSGC and previous classification schemes for reporting salivary gland FNA specimens is the introduction of “SUMP” category; this significantly lowers the ROM of cases classified as either benign or negative for malignancy 29,40 . Both benign and malignant salivary gland neoplasms have significant morphological overlap and can be difficult to classify even after resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation